1995
DOI: 10.1093/geront/35.1.127
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Visual Barriers on Exiting Behavior In a Dementia Care Unit

Abstract: Exiting due to wandering was a problem for caregivers in this dementia care unit. Previous attempts to control exiting by wanderers proved ineffective. We manipulated the view and light through a window using visual barriers: window blind, cloth barrier, and a combination of the two. The closed blind reduced exiting by 44%. The cloth barrier was the most effective solution, reducing exiting by 96%. The combination of the blind and cloth barrier reduced exiting 88%. These findings support those of Namazi, Rosne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Camouflage interventions are those that try to hide the exits, whether portraying them as shelves, 7 miniblinds or panels, 9 or as a painted mural. 11 The last two had positive impacts, as they reduced the frequency of exit attempts and door testing.…”
Section: Resultsmentioning
confidence: 99%
“…Camouflage interventions are those that try to hide the exits, whether portraying them as shelves, 7 miniblinds or panels, 9 or as a painted mural. 11 The last two had positive impacts, as they reduced the frequency of exit attempts and door testing.…”
Section: Resultsmentioning
confidence: 99%
“…A set of six early studies emerged from the literature search which involved disorientating people with dementia by providing distracting cues away from the exit door of residential facilities. These included environmental strategies such as distracting grid patterns of black tape ( Chafetz, 1990 ; Hewawasam, 1996 ; Hussain & Brown, 1987) or covering up the exit door with a blind ( Dickinson, McLain-Kark, & Marshall-Baker, 1995 ), mirrors ( Mayer & Darby, 1991 ) or a wall mural ( Kincaid & Peacock, 2003 ). Whilst all but one ( Chafetz, 1990 ) found significant effects of these barriers on exit-seeking behaviour, this raises an important issue: who is this for?…”
Section: Resultsmentioning
confidence: 99%
“…Masking the doorknob by painting it the same color as the door to minimize the color contrast and create a camouflage condition and the use of a doorknob cover (allowed the knob to turn only when pressure was applied) were less successful than concealment, but more effective than the use of grid tape patterns. Dickinson et al (1995) found that mini-blinds covering the door windows using the same color to match the door was only marginally significant in reducing exiting attempts (exiting attempts decreased from 115 times to 64 attempts: a reduction of 44%). However, the use of a cloth barrier to cover door hardware, similar to the one used by Namazi et al (1989) to match the door and frame color, was found to be more effective (a reduction of 96% from baseline).…”
Section: Door Hardware and Window Camouflagementioning
confidence: 97%
“…Also for the purposes of this review, exit doors within the institutional setting are considered part of a means of egress, usually leading from the floor area they serve to a separate building, an open public thoroughfare, or an exterior open space. Methods of preventing or limiting PWD from walking with purpose in healthcare and institutional settings have included alarms, locking external doors, physical restraint, or chemical restraint with the use of sedating medications (Dickinson et al, 1995; Namazi et al, 1989). Dickinson and McLain-Kark (1998) note that chemical restraint to prevent exiting behaviors “is only a temporary solution if the exiting is associated with the design of the facility” (p. 24).…”
mentioning
confidence: 99%